The Global restructuring of agro-food systems - McMichael, Philip (Food systems and agrarian change., 1994)
Across the world, food systems and agricultural systems are changing at a phenomenal rate. Widespread restructuring has not been confined to the production and distribution of food, though; many regions and even nations are undergoing social, political, and economic transformation as well. Bringing together twelve essays by scholars from a number of disciplines, I this timely book documents the interdependence of food systems, nation states, and the world economy. Stressing the political foundations of global agro-food systems, it sheds light on such complex questions as whether today's changes in food and agrarian systems anticipate a new world order, or are merely efforts to preserve an old order in crisis.